Musculoskeletal disorders among recyclers working in Metropolitan Lima - Morales Quispe, Juan (2016)
Introduction: Recyclers mostly operate in poor sanitary conditions and low occupational safety. The symptoms of musculoskeletal disorders (MSD) represent a problem affecting all the sectors and occupations. Objective. To determine the perception of MSD symptoms. Design. Cross-sectional study. Setting. Metropolitan Lima. Participants. Recyclers of any age and gender. Interventions. Implementation of Nordic Questionnaire. Main outcome measures. Presence of MSD symptoms according to anatomical regions. Results. Out of 131 selected participants, 114 met the inclusion criteria of which 58.8% (n = 67) were male and 41.2% (n = 47) female with an average age of 41.2 years (SD: 14.61; min: 18, max: 77). The anatomical region where most of the symptoms occurred was the lumbar region where the disease interfered with most of the household chores or work. In the age group 20-39 years, the most frequent musculoskeletal symptoms occurred in the cervical region (p = 0.012), whereas among people older than 50 years they occurred in the knees (p = 0.040). Conclusions. The perception of the symptoms of musculoskeletal disorders among recyclers was predominantly present in the lumbar region and it was the disease that had the most interference with household chores or work.